Effect of MWNTs and SiC-Coated MWNTs on Properties of PEEK/LCP Blend - Ganesh Chandra Nayak; R. Rajasekar; Saswata Bose; Chapal Kumar Das (Journal of Nanotechnology)
Multiwall carbon nanotubes (MWNTs) were modified with polycarbosilane-derived silicon carbide (SiC) to improve its dispersion in the polymer matrix. PEEK/LCP/MWNTs nanocomposites were prepared by melt blending. TEM images show the improved dispersion of SiC-coated MWNTs against agglomerated structure of pure MWNTs in the blend. FESEM images shows better fibrillation of LCP in presence of SiC-coated MWNTs. TGA reveals that nanocomposites with SiC-coated MWNTs shows higher thermal stability than MWNTs filled blend system. Based on enhanced dispersion, storage modulus, tensile modulus and tensile strength were increased drastically with the incorporation of SiC-coated MWNTs. Glass transition temperature of the nanocomposites shows significant improvement with the incorporation of MWNTs.